Strategi Meningkatkan Literasi Membaca Anak Usia Dini Dengan Perpustakaan Keliling: Studi Kasus Di Desa Harjamekar - Edliawati, Desi; Romadhona, Desty; Putri, Elvyana; Hikmah, Mia Aulia; Pebriyanto, Joko Pebriyanto (CV. ITTC INDONESIA, 2024)
The importance of early literacy in children's growth and development, focused on Real Work Lecture (KKN) activities in Harjamekar Village, Bekasi Regency. Literacy, especially the ability to read, is very important for the development of critical and creative thinking patterns in children. The implementation method used includes the time and place of implementation, the parties involved, the data collection process, and data analysis. This research highlights the challenge of low interest in reading in Indonesia, especially in the eastern region, and how mobile library programs can play a role in increasing access to literacy. This program involves collaboration between KKN students, the government, mobile libraries and local communities to provide facilities and literacy training. The evaluation results show that this program has succeeded in increasing children's interest and ability to read, as demonstrated by participants' enthusiasm and increased ability to understand and relate to the content they read.